ANALISIS PERTUMBUHAN DAN PRODUKSI PADI GOGO AROMATIK LOKAL DENGAN APLIKASI KOMPOS JERAMI PADI PADA SISTEM PERTANAMAN LORONG DAN MONOKULTUR - Muhammad Kadir; Rajony Aty; Syamsia Syamsia (Fakultas Pertanian, Universitas Janabadra, 2023)
Aromatic upland rice is currently planted with an Alley Cropping system to get around land limitations. To compare how the growth and production response compared to the monoculture system on the application of composted organic fertilizer, a field experiment was conducted to evaluate and analyze the effect of various doses of composted organic fertilizer on the growth and production of local aromatic upland rice grown in Monoculture and Alley Cropping systems. The experiment was conducted in a Randomized Complete Block Design (RCBD) to test four doses of compost fertilizer, namely 0, 4, 8, and 16 tons/ha, respectively, in both cropping systems. The results showed that the analysis of growth and generative components of local aromatic upland rice with Alley Cropping and Monoculture cropping systems were better in the application of compost 15 tons per hectare. The highest average yield of local aromatic upland rice when compared between Alley Cropping and Monoculture planting is still the highest Monoculture system with the average Dry grain weight per hectare with 15 tons/ha Compost in this experiment which is 4,141.61 kg of grain/ha while planting the Alley Cropping system only produces an average of 917.69 kg/ha. INTISARIPadi gogo Aromatik saat ini banyak ditanam dengan sistem Alley Cropping menyiasati keterbatasan lahan. Untuk membandingkan bagaimana respon pertumbuhan dan produksi dibandingkan dengan sistem monokultur pada pengaplikasian Pupuk organic Kompos, maka sebuah Percobaan lapangan dilakukan untuk mengevaluasi dan menganalisis pengaruh berbagai dosis pupuk organik kompos terhadap pertumbuhan dan produksi padi gogo aromatic lokal yang ditanam pada sistem Monokultur maupun Alley Cropping. Percobaan dikakuakn dalam Rancangan Acak Kelompok Lengkap (RAKL) untuk menguji Empat dosis pupuk kompos yaitu 0, 4, 8, dan 16 ton/ha, masing-masing pada kedua sistem pertanaman. Hasil menunjukkan bahwa pertumbuhan dan Komponen generatif padi gogo aromatik lokal dengan sistem pertanaman Alley Cropping maupun Monokultur yang lebih baik adalah pada aplikasi kompos 15 ton per hektar. Rata-rata produksi padi gogo aromatik lokal tertinggi jika dibandingkan antara pertanaman Alley Cropping dan Monokultur yang trtinggi masih ssitem Monokultur dengan rata-rata bobot gabah Kering per hektar dengan aplikasi kompos jerami padi sebanyak 15 ton/ha pada percobaan ini yaitu 4.141,61 kg gabah/ha sementara penanaman sistem Alley Cropping hanya menghasilkan rata-rata 917.69 kg.